Hematochezia in Patient with Colorectal Polyps - Ellen Susanti; Ari Fahrial Syam; Murdani Abdullah; Vera Yuwono (The Indonesian Society for Digestive Endoscopy, 2004)
More than 95% colorectal cancers arise from neoplastic adenomatous polyps (adenomas). The malignant potential of polyps depends on size, amounts, histological type and degree of dysplasia. The prevalence of adenoma increases with age. Patient whose age more than 40 years old with rectal bleeding as presenting symptom should never be ascribed solely to coexisting haemorrhoids without a through evaluation of the colon and rectum. We reported a case of hematochezia due to colorectal polyps with coexisting hemorrhoids as suspected bleeding source. Colonoscopy examination demonstrated colorectal adenomatous polyps in rectum and sigmoid. Polypectomy was done and tissue biopsy Result was tubular adenoma with mild dysplasia. Keywords: Adenomatous polyp, hematoschezia